La convivencia familiar y la disciplina de los estudiantes en la Unidad Educativa "Quito Sur", periodo 2017-2018. - Cando Cuenca, Irlanda Ruth (2018)
The research project about coexistence family and the discipline of student was developed with the purpose of identifying the factors of coexistence family that have an impact on the discipline of students, considering that the family environment is the first scenario in which students learn the rules, behaviors and behaviors to achieve a harmonious coexistence in the educational environment with their classmates and their teachers. The research problem is the inadequate level of discipline that have the students of the sixth year of basic education, which generates a problem in the school coexistence, students present situations of aggression among classmates, negative attitudes, lack of respect, bad discipline and bad interpersonal relationships in the classroom. The objectives of the research focus on the study of the factors of family coexistence, such as parental parenting styles and the family structure to determine its impact on student discipline. The methodology applied in the research focused on the quantitative approach, the deductive-inductive, analytical-synthetic method, the documentary and field design for the abstraction of the theoretical and empirical information that is required in the development of research. The research is important for the education of the students, seeing that a change in the coexistence family and in the discipline benefits to teachers and students of the sixth year of Basic Education at “Quito Sur” Educational Unit in the short time, owing to it takes a change in family and school relationships, improving coexistence between parents and children, between teachers and students, through better interpersonal communication, more respect and tolerance.